Psychometric Properties of the Turkish Version of Prolapse and Incontinence Knowledge Questionnaire - Arife Korkut; Ilkim Citak Karakaya; Semiha Yenisehir; Mehmet Gurhan Karakaya (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: This study aimed to translate and culturally adapt the prolapse and incontinence knowledge questionnaire into Turkish, and to investigate the psychometric properties of the Turkish version prolapse and incontinence knowledge questionnaire.